Recent developments in offshore wind energy systems: Technologies and practices - Saravanan Vasudevan; Venkatachalam Moorthy Kondayampalayam; Arumugam Murugesan (Institute of Advanced Engineering and Science, 2022)
This paper deals with offshore wind power generation technologies, power transmission and grid communication features, and associated power system studies for effective implementation of offshore wind energy systems, explaining its various stages of implementation. Also, this paper reviews the latest trends in offshore wind energy systems, addressing various aspects like large wind farm siting, power evacuation studies, cable selection, high-voltage direct current/flexible alternating current transmission systems (HVDC/FACTS) technology options, reliability evaluation, and autonomous monitoring. India's renewable power generation capacity through off-shore wind generation is also outlined to ensure low carbon energy emissions with improved energy efficiency. The policy and regulatory framework factors for reaching five gigawatts (GW) of offshore wind projects in the states of Tamil Nadu and Gujarat by the year 2032 using current methods and advanced technology are discussed here. This goal can be accomplished using current practices and advanced technologies. For effective implementation of offshore wind farms, suitable measures and likely actions by various stakeholders are suggested.